THE ANALYSIS OF INFORMATION SEEKING BEHAVIOUR OF THE TEACHERS OF ŠIAULIAI STATE UNIVERSITY of APPLIED SCIENCES - Gasparaitytė, Gerda; Jakutienė, Rita (PROFESSIONAL STUDIES: Theory And Practice, 2022)
Annotation Information is a basic human need. Information is necessary for socio-economic development. Information seeking behaviour is defined as the area related to the identification of user information needs, seeking behaviour, and subsequent use of information. Information seeking occurs when a person realizes the need to acquire contextual information and consciously takes action to meet that need. The research on information behaviour has evolved in various directions and maintained its popularity. Information behaviour research provides a better understanding of how people actually use information in all aspects of life, improving the analysis of information behaviour, processes, and systems in different information spaces. Information behaviour models attempt to describe information seeking activities, the causes and consequences of these activities, or the relationships between the stages of information seeking behaviour. The article presents the research of information seeking behaviour of the teachers of Šiauliai State University of Applied Sciences. In order to study information behaviour of Šiauliai State University of Applied Sciences teachers, an information behaviour model was developed based on T. D. Wilson, Othishi-Gottschalg-Duque information behaviour models, where the main elements are user information needs, information sources, information seeking process and information seeking obstacles. The survey was chosen as the data collection method. A questionnaire with the same content was provided to all the respondents. The questionnaire contained 15 questions aimed at identifying specific facts relevant to the research. 108 questionnaires were sent to the academic staff of Šiauliai State University of Applied Sciences, which they were asked to fill in electronically. 73 questionnaires were submitted. Key words: information behaviour, information seeking behaviour, information behaviour models, teachers, use of information.